American Dreams on the Frontiers Community in Cather's My Antonia - Abbas Abbas; Fathu Rahman; M. Amir Pattu; Asriani Abbas; Basrah Gising (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Literature is a space to express sociological issues that are absorbed by the author in the society around him/her as a social phenomenon. The research in this article is a sociological literary research which aims to present the issue of American Dreams values in the novel My Antonia which are absorbed from Willa Cather's sociological experience in American frontier communities in the late 19th to early 20th centuries. American Dreams is a spirit that binds common ideals in order to unite the heterogeneity of the American people into a superior nation in various aspects of life. The issue of American Dreams in the novel My Antonia is analyzed using a scientific method called the Literary Sociology Approach. It emphasizes the author's imagination to literary works have genetics in human sociological life to document certain phenomena in certain societies. Researchers found 7 out of 10 American Dreams values in the spirit of frontier people in the western region of America as documented in the novel My Antonia by Willa Cather, namely Liberty, Democracy, Equality, Opportunity, Education, Progress, and Peace. Liberty is the freedom to determine one's own destiny, Democracy is the right to express one's desires as an independent person, Equality is equal treatment before the law, Opportunity is taking advantage of opportunities for the nation progress, Education is the spirit of seeking knowledge to create new discoveries, Progress is actualizing all potential to achieve prosperity, and Peace is the upholding of human rights to maintain the universal security of humanity.